So x2 - 6x + 9 = 0, Factorises as (x - 3)(x - 3) so only solution is x = 3
(9,6)
6x plus 3 equals 8x plus 14 when solved mathematically is equal to x = -5.5.
-6x
x=10
The quadratic expression x2+6x+8 when factorised equals (x+2)(x+4)
The answer is 258x
(9,6)
6x+x = 7x
6x plus 3 equals 8x plus 14 when solved mathematically is equal to x = -5.5.
-6x
x=10
6x
The quadratic expression x2+6x+8 when factorised equals (x+2)(x+4)
6x+4=52 6x=48 x=8
6x plus 3y minus 2x plus 5y equals 4x plus 8y.
It is: 3x2+6x-11 = 0
5x + x - 6x + 2x = 2x